Sliding Wear and Friction Properties of Al-Graphene Composites under Oil Lubrication - Senel, Mahmut Can; Gurbuz, Mevlut (Springer, 2025)
In this work, Al-graphene composites were fabricated using the powder metallurgy route. This technique includes ultrasonic stirring, mechanical stirring, ball milling, filtering, drying, pressing, and heat-treatment. The influence of graphene amount (0.1-0.5 wt.%) on the microstructural, mechanical, and tribological behavior under oil lubrication was examined. The highest density (2.52 g/cm3), tensile stress (119 MPa), and hardness (57 HV) were obtained at Al-0.1% graphene composite. The minimum mass loss (0.2 mg) and wear rate (1.57 x 10-5 mm3/(Nm)) were detected at Al-0.1% graphene for a 10 N load under oily conditions. Also, a minimum friction coefficient (0.018) was obtained in Al-0.5% GNPs under oily conditions. As a result of the tests carried out, graphene addition enhances the wear resistance and mechanical strength of the composites up to 0.1 wt.% content. After 0.1% graphene amount, the properties of the specimens deteriorated on account of the accumulation of graphene.
Keywords: Aluminum; Composite; Friction; Graphene; Strength; Wear